1980
DOI: 10.1039/p29800001473
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening of some radicals containing the cyclopropylmethyl system

Abstract: Mono-and bi-cyclic radicals containing the cyclopropylmethyl system are readily generated by interaction of the appropriate halides with triphenyl-or tributyl-stannane. Each radical studied underwent ring-opening by fission of the more substituted By-bond. In the case of the secondary radical (12b) the new double bond was formed preferentially in the trans-configuration. Rate constants, which cannot be determined with high accuracy by this method, lie in the range I x 10'-3 x 1 O8 s-l at 25 "C. When generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…Cyclopropyl-appended ACV variants have been used to probe the radical nature of the thiazolidine closure reaction in solution. [42] The cyclopropyl group is a useful probe for radicals as it readily forms but-3-enyl systems via a cyclopropylcarbinyl radical intermediate species, [43] the formation of which would lead to substrate conversion to an unsaturated macrocyclic product. [41,42] Extending this into crystallographic studies, Howard-Jones et al (2007) worked with ACV analogues incorporating cyclopropyl groups in the third residue: δ-(l-α-aminoadipoyl)-l-cysteinyl-β-methyl-d-cyclopropylglycine (ACmcpG, 30; Figure 16A) and δ-(l-α-aminoadipoyl)-l-cysteinyl-d-cyclopropylglycine (ACcpG, 32; Figure 16B).…”
Section: Substrate Analogues With Altered Steric Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclopropyl-appended ACV variants have been used to probe the radical nature of the thiazolidine closure reaction in solution. [42] The cyclopropyl group is a useful probe for radicals as it readily forms but-3-enyl systems via a cyclopropylcarbinyl radical intermediate species, [43] the formation of which would lead to substrate conversion to an unsaturated macrocyclic product. [41,42] Extending this into crystallographic studies, Howard-Jones et al (2007) worked with ACV analogues incorporating cyclopropyl groups in the third residue: δ-(l-α-aminoadipoyl)-l-cysteinyl-β-methyl-d-cyclopropylglycine (ACmcpG, 30; Figure 16A) and δ-(l-α-aminoadipoyl)-l-cysteinyl-d-cyclopropylglycine (ACcpG, 32; Figure 16B).…”
Section: Substrate Analogues With Altered Steric Profilesmentioning
confidence: 99%
“…Cyclopropyl‐appended ACV variants have been used to probe the radical nature of the thiazolidine closure reaction in solution [42] . The cyclopropyl group is a useful probe for radicals as it readily forms but‐3‐enyl systems via a cyclopropylcarbinyl radical intermediate species, [43] the formation of which would lead to substrate conversion to an unsaturated macrocyclic product [41,42] . Extending this into crystallographic studies, Howard‐Jones et al.…”
Section: Crystal Structures Of Ipns Complexes With Substrate and Product Analoguesmentioning
confidence: 99%
“…(11) (Scheme 2) became important at longer reaction times, as did a tribromide; probably (12). Retention time comparisons with authentic l-bromobicyclo[2.1.l]hexane (13) showed that none was detectable, i.e. the mol % of (13) was d 0.5.…”
Section: -Bromobicyclo[211]hexane (9) But the Dibromides (10) Andmentioning
confidence: 99%
“…Previous reports,'-5 have demonstrated that cyclobutylmethyl (and substituted cyclobutylmethyl) radicals (1) are prone to rapid ring-opening to give the isomer 2 by a process which is frequently, though not always,' irreversible. The rate constant for ring fission of the parent species 1,' for example, is 4.7 x lo3 s-' at 25 "C, and the activation energy of the rearrangement 1 -2 is 11.7 kcal mol-' (1 cal SE 4.18 J).…”
mentioning
confidence: 99%